Strategies to deal with the COVID-19 pandemic - Paulo NADANOVSKY; Ana Paula Pires dos SANTOS (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The World Health Organization declared a COVID-19 pandemic on March 11, 2020, when there were 4,293 confirmed cumulative deaths. By May 17, 2020 this number increased to 315,005. The risk of death is higher above the age of 60, but there are many deaths below 60 (for example, in Sao Paulo, 25%). Due to the lack of a vaccine or specific treatment, there are at least three types of interventions used in the first wave of this pandemic: increased alertness and hygiene (e.g. Sweden); identification and isolation of infected people and their contacts (e.g. South Korea); lockdown (e.g. Italy). These interventions are complementary. Choices of the right mix of interventions will vary from society to society and in the same society at different times. The search for a miracle drug is dangerous because it is based on the mistaken belief that any treatment option is better than "nothing". Brazilian society will not be able to maintain lockdown for a long period. Naturally, in the near future, regardless of the advice from scientists, doctors and authorities, commerce, services and schools will reopen. In order to implement any strategy aimed to control the pandemic and preserve the economy, the country needs leadership that centralizes and coordinates actions. Unfortunately, the Brazilian government is not fulfilling this role; on the contrary, it is a hindrance. This negative leadership and lack of coordination are causing many deaths and are severely damaging the lives of survivors by delaying the resuming of economic and social activities.